Ultrasound in Emergency Care. - Brooks, Adam, 1969- (John Wiley & Sons, 2008)
A practical guide to the use of ultrasound and how to interpret the scans, aimed specifically at emergency physicians and staff. This is recognised as an essential skill in emergency medicine, and this book will provide the means to learn it, with question led text and many illustrations of real examples. The book will include a CD Rom of video clips, showing normal and abnormal scans, approximating to the real life situation.